f(x) = 2^(4x)
g(x) = 2^x
(fg) = 2^4x * 2^x = 2^5x
NOTE: When multiplying two powers with same base exponents add.
(f/g)(x) = (2^4x)/(2^x) = 2^3x
NOTE: And when dividing they subtract.
Answer: a and c
//Hope it helps.
Answer:
c
Step-by-step explanation:
if I understand this right, then the expression is
2×sqrt(28) - 5×sqrt(63)
let's look for squared factors in the numbers under the square roots.
28 = 4×7 (4 is a squared number)
63 = 9×7 (9 is a squared number)
so,
2×sqrt(4×7) - 5×sqrt(9×7) =
= 2×2×sqrt(7) - 5×3×sqrt(7) = 4×sqrt(7) - 15×sqrt(7) =
= (4 - 15)×sqrt(7) = -11×sqrt(7)
4 & 6 cause one of both of them got eaten
The correct answer is 120 degrees.
With the bigger triangle you can add all of the angles to get 60 degrees. (35+25)
This leaves you with a 120 degrees angle in the unmarked corner of the triangle. Any horizontal line and any triangle is 180 in total.
So with a 120 degree angle in the corner this leaves us with a 60 angle in the smaller triangle. ( The smaller triangle equals 60 degrees in all corners, it is equalateral ).
X is on a horizontal line and we now know that the one side of the line equals 60 degrees and any horizontal line equals 180 in total, this means that the measure of X is 120, (60+120)
X is 120 :)
L*W*H
take them all and multipy